2020
DOI: 10.3390/biology9120424
|View full text |Cite
|
Sign up to set email alerts
|

Determining Soil Microbial Communities and Their Influence on Ganoderma Disease Incidences in Oil Palm (Elaeis guineensis) via High-Throughput Sequencing

Abstract: Basal stem rot (BSR), caused by Ganoderma boninense, is the most devastating oil palm disease in South East Asia, costing US$500 million annually. Various soil physicochemical parameters have been associated with an increase in BSR incidences. However, very little attention has been directed to understanding the relationship between soil microbiome and BSR incidence in oil palm fields. The prokaryotic and eukaryotic microbial diversities of two coastal soils, Blenheim soil (Typic Quartzipsamment—calcareous she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 110 publications
1
11
0
1
Order By: Relevance
“…Organic matter is a source of food for soil microorganisms, so if a soil has a low organic matter content, the abundance of health agents will also be low, while the population of G. boninense will continue to increase. This is also in line with what was explained by Susanto et al (2013) and Goh et al (2020), that the role of organic matter in suppressing the development of pathogens is not only by increasing soil microbial activity, but also by improving root health to make plants more resistant to disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Organic matter is a source of food for soil microorganisms, so if a soil has a low organic matter content, the abundance of health agents will also be low, while the population of G. boninense will continue to increase. This is also in line with what was explained by Susanto et al (2013) and Goh et al (2020), that the role of organic matter in suppressing the development of pathogens is not only by increasing soil microbial activity, but also by improving root health to make plants more resistant to disease.…”
Section: Discussionsupporting
confidence: 92%
“…Soil CEC describes the ability of the soil to hold or absorb plant nutrients in the form of cations available to plants, so the higher the CEC value, the more nutrients it can absorb (Nazari et al, 2020). However, soils that were severely exposed to basal stem rot disease had higher CECs than Ganoderma suppressive soils (Goh et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…These soil-dwelling microorganisms comprise different taxa, such as bacteria, arbuscular mycorrhizal fungi (AMF), actinomycetes, and cyanobacteria [30]. Important characteristics of these microbes include improving root systems, production of organic acids, phytohormones, antibiotics, siderophores, volatile bacterial compounds, solubilization of phosphorus, nitrogen-fixing, carbon cycling, and disease prevention [4,14]. The activities of these helpful microbes can be restricted by the soil's acidity, except for fungi, which may thrive in a broad range of soil pH [9].…”
Section: Impacts On Soil Microbial Communities and Biological Processesmentioning
confidence: 99%
“…The rising worldwide demand for palm oil has prompted an expansion in agricultural land dedicated to industrial oil palm cultivation [1,2]. This industrial expansion in the major palm oil-producing and exporting countries, such as Malaysia in Southeastern Asia, has resulted in massive conversion of existing agricultural lands and deforestation of tropical rainforests [3,4]; however, soil acidity and nutrient depletion are two major constraints in oil palm cultivation in tropical regions [5][6][7][8]. This is primarily because acidic soil increases the leaching of many essential plant nutrient elements and the availability of toxic elements by modifying various geochemical and biological reactions in the soil [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Daza et al (2020) showed that with auxins, in particularly NAA and 2,4-D, it is feasible to produce good bunch of parthenocarpic fruits without having to rely on pollination. With its striking characteristics and the need to diversify the current guineensis-based planting materials, more efforts are being channelled to further unravel the oleifera and its hybrids for future applications (Ting et al, 2020b;Zulkifli et al, 2020).…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%